Add all the numbers to get 36 and divide by the amount of numbers to get your answer. 6.
Answer:
See explanation
Step-by-step explanation:
Triangle ABC ha vertices at: A(-3,6), B(0,-4) and (2,6).
Let us apply 90 degrees clockwise about the origin twice to obtain 180 degrees clockwise rotation.
We apply the 90 degrees clockwise rotation rule.
![(x,y)\to (y,-x)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%20%28y%2C-x%29)
![\implies A(-3,6)\to (6,3)](https://tex.z-dn.net/?f=%5Cimplies%20A%28-3%2C6%29%5Cto%20%286%2C3%29)
![\implies B(0,4)\to (4,0)](https://tex.z-dn.net/?f=%5Cimplies%20B%280%2C4%29%5Cto%20%284%2C0%29)
![\implies C(2,6)\to (6,-2)](https://tex.z-dn.net/?f=%5Cimplies%20C%282%2C6%29%5Cto%20%286%2C-2%29)
We apply the 90 degrees clockwise rotation rule again on the resulting points:
![\implies (6,3)\to A''(3,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%286%2C3%29%5Cto%20A%27%27%283%2C-6%29)
![\implies (4,0)\to B''(0,-4)](https://tex.z-dn.net/?f=%5Cimplies%20%284%2C0%29%5Cto%20B%27%27%280%2C-4%29)
![\implies (6,-2)\to C''(-2,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%286%2C-2%29%5Cto%20C%27%27%28-2%2C-6%29)
Let us now apply 90 degrees counterclockwise rotation about the origin twice to obtain 180 degrees counterclockwise rotation.
We apply the 90 degrees counterclockwise rotation rule.
![(x,y)\to (-y,x)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%20%28-y%2Cx%29)
![\implies A(-3,6)\to (-6,-3)](https://tex.z-dn.net/?f=%5Cimplies%20A%28-3%2C6%29%5Cto%20%28-6%2C-3%29)
![\implies B(0,4)\to (-4,0)](https://tex.z-dn.net/?f=%5Cimplies%20B%280%2C4%29%5Cto%20%28-4%2C0%29)
![\implies C(2,6)\to (-6,2)](https://tex.z-dn.net/?f=%5Cimplies%20C%282%2C6%29%5Cto%20%28-6%2C2%29)
We apply the 90 degrees counterclockwise rotation rule again on the resulting points:
![\implies (-6,-3)\to A''(3,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%28-6%2C-3%29%5Cto%20A%27%27%283%2C-6%29)
![\implies (-4,0)\to B''(0,-4)](https://tex.z-dn.net/?f=%5Cimplies%20%28-4%2C0%29%5Cto%20B%27%27%280%2C-4%29)
![\implies (-6,2)\to C''(-2,-6)](https://tex.z-dn.net/?f=%5Cimplies%20%28-6%2C2%29%5Cto%20C%27%27%28-2%2C-6%29)
We can see that A''(3,-6), B''(0,-4) and C''(-2,-6) is the same for both the 180 degrees clockwise and counterclockwise rotations.
Answer:
We'd need to know the coordinates of the line segment.
Step-by-step explanation:
I am not sure what your problem here is.
you understand the inequality signs ?
anyway, to get
6×f(-2) + 3×g(1)
we can calculate every part of the expression separately, and then combine all the results into one final result.
f(-2)
we look at the definition.
into what category is -2 falling ? the one with x<-2, or the one with x>=-2 ?
is -2 < -2 ? no.
is -2 >= -2 ? yes, because -2 = -2. therefore, it is also >= -2.
so, we have to use
1/3 x³
for x = -2 that is
1/3 × (-2)³ = 1/3 × -8 = -8/3
g(1)
again, we look at the definition.
into what category is 1 falling ? the one with x > 2 ? or the one with x <= 1 ?
is 1 > 2 ? no.
is 1 <= 1 ? yes, because 1=1. therefore it is also <= 1.
so we have to use
2×|x - 1| + 3
for x = 1 we get
2×0 + 3 = 3
6×f(-2) = 6 × -8/3 = 2× -8 = -16
3×g(1) = 3× 3 = 9
and so in total we get
6×f(-2) + 3×g(1) = -16 + 9 = -7